Efforts to Prepare Graduates Ready to Work Through Specialization in Edupreneurship Courses in the Islamic Religious Education Study Program - Afifah; Imroatun Adila (Penerbit Presisi Pustaka, 2025)
The unemployment rate in Indonesia is relatively high, so this is a reason for every campus to prepare work-ready graduates to enter the world of work after college. UNIA ( Al-Amien Prenduan University) is also one of the campuses that prepares work-ready graduates through educational specialization courses in the PAI study program. This thesis uses a descriptive qualitative method with data collection techniques through interviews, observation and documentation. The findings of this research are based on two focuses; First, efforts to prepare graduates ready for work through edupreneurship specialization courses for PAI students, Tarbiyah Faculty, Al-Amien Prenduan University, namely; Making edupreneurship a formal learning and specialization subject, explaining learning objectives, placing qualified lecturers in edupreneurship learning, using brainstorming methods, applying theoretical and practical learning, and evaluating learning. Second, supporting factors in this effort are; There are lecturers who are qualified in edupreneurship, the commitment of the head of study program and all lecturers in providing and guiding learning, as well as the enthusiastic, corious and open-minded attitudes of female students during the learning process. Meanwhile inhibiting factors include; Inadequate facilities and student boarding regulations.